The new trends in wild edible plants valorization: commercial cultivation protocols, agronomic practices and future challenges - Polyzos, Nikolaos; Liava, Vasiliki; Antoniadis, Vasileios; Garcia, Pedro; Alexopoulos, Alexios A.; Petropoulos, Spyridon A. (Frontiers in Horticulture, 2025)
The ongoing environmental crisis that takes place during the last years necessitates the adjustment of cultivations practices and their transition to sustainable and eco-friendly cropping systems system. In this context, the adoption of innovative techniques, as well as the integration of wild edible plants (WEPs) in modern farming systems is a promising strategy to cope with modern challenges that the agricultural sector has to face due to climate change. The Mediterranean basin is a valuable hotspot of WEPS and presents an abundant biodiversity of such species with several authors highlighting the potential prospects of valorizing WEPs as complementary/alternative crops due to their wide range of adaptability and the minimal requirements for agriculture inputs. Apart from the agronomic aspects, WEPs are highly appreciated for their numerous health benefits and they could be an interesting addition in the market niche for super and healthy foods that modern consumers are increasingly seeking. Therefore, their exploitation through commercial cropping systems could be a viable solution towards overcoming the ongoing climate crisis while safeguarding food security, especially in the arid and semi-arid regions of the Mediterranean basin where the cultivation of conventional crops is severely compromised. Considering the increasing scientific interest on WEPS during the last years, this review aims to highlight the recent scientific trends regarding the implementation of in vitro techniques for the propagation of these species. Moreover, the optimum cultivation practices and agronomic aspects of selected WEPs and sum up the most up-to date information regarding their integration in modern cropping systems as part of the climate mitigation strategies. The response of WEPS to abiotic stressors (e.g. salinity, heat, drought) is also discussed, considering the capability of these species to adapt under unfavorable conditions, as well as the potential use of WEPS for phytoremediation purposes. Finally, the future challenges and the next steps for further valorization of WEPs will be also discussed.